Parental Perceptions of STEM Enrichment for Young Children. (March 2018) - Tay, Juliana; Salazar, Alissa; Lee, Hyeseong
Most pre-kindergarten (pre-K) and kindergarten curricula are challenging and engaging, but few are strongly grounded in science, technology, engineering, and mathematics (STEM) education. In this study, the authors examined parental perception ( N = 55) of the influences of a Saturday STEM enrichment program in one university center on pre-K and kindergarten students and their attitudes toward STEM learning. Using survey data collected from 2013 to 2016, the authors studied parental comments about benefits, drawbacks, and memorable moments they observed from their children's experiences during the program. These comments were analyzed qualitatively using NVivo, and three main themes were developed. The themes were children's reactions to STEM learning, meeting the needs of young gifted learners, and learning beyond the classroom. These themes reinforced current literature in the field showing young children's need for STEM education. Sadly, few opportunities for STEM-focused programming for young children exist.